Controllability of nonlinear discrete systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
Local constrained controllability problems for nonlinear finite-dimensional discrete 1-D and 2-D control systems with constant coefficients are formulated and discussed. Using some mapping theorems taken from nonlinear functional analysis and linear approximation methods, sufficient conditions for constrained controllability in bounded domains are derived and proved.
Keywords: nonlinear systems; discrete systems; 2-D systems; controllability; nonlinear covering operators